2018
DOI: 10.1111/1346-8138.14683
|View full text |Cite
|
Sign up to set email alerts
|

Impact of chronic urticaria on systemic lupus erythematosus: A nationwide population‐based study in Taiwan

Abstract: Chronic urticaria (CU) may be closely pathogenically related to systemic lupus erythematosus (SLE). This study aims to investigate the association between CU and SLE patients in Taiwan. A nationwide population‐based cohort study from 1997 to 2013 was conducted. Investigated subjects were selected from the Taiwan National Health Insurance Research Database using the International Classification of Disease, Ninth Revision code. Participants consisted of 13 845 subjects newly diagnosed with CU from 2003 to 2013. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…As confirmed by a literature review, our study is the first nationwide-cohort study that demonstrates an association between T1DM and urticaria in children. Furthermore, our data demonstrates that T1DM is a significant risk factor for urticaria, regardless of urbanization level, income, and presence of inflammatory bowel disease; factors that have also been reported to be related to urticaria [28,29] A similar association between T1DM and urticaria was not observed in adults in this study. This may be because we excluded those diagnosed with urticaria before enrollment into the study.…”
Section: Discussionsupporting
confidence: 66%
“…As confirmed by a literature review, our study is the first nationwide-cohort study that demonstrates an association between T1DM and urticaria in children. Furthermore, our data demonstrates that T1DM is a significant risk factor for urticaria, regardless of urbanization level, income, and presence of inflammatory bowel disease; factors that have also been reported to be related to urticaria [28,29] A similar association between T1DM and urticaria was not observed in adults in this study. This may be because we excluded those diagnosed with urticaria before enrollment into the study.…”
Section: Discussionsupporting
confidence: 66%
“…The SLE event was defined as diagnosis with ICD-9-CM code 710.0 (at least one hospital admission or three outpatient visits) and using HCQ within one year after diagnosis. 2528 As a result, the data for the diagnosis of SLE should be accurate and reliable. However, the number of new SLE cases was rather small, despite the large number in both cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…This condition affects approximately one‐third of women during their lives and is the most common reason for reproductive‐aged women to seek medical care 12–14 . Previous studies have found the relationship between AUB with various immune‐mediated diseases 15–18 . Patients with AUB have also been reported to be associated with CSU.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] Previous studies have found the relationship between AUB with various immune-mediated diseases. [15][16][17][18] Patients with AUB have also been reported to be associated with CSU. However, the evidence is limited to either case reports or cross-sectional studies.…”
Section: Introductionmentioning
confidence: 99%